Popular vegetarian diets in China: a sustainable dietary option for the globe? - Yaxian Zhang; Wenpeng Du; Wenpeng Du; Xiaozhi Xiang; Xiaozhi Xiang; Manxiang Ji; Xiaqing Wang (Frontiers in Sustainable Food Systems)
Vegetarian practices have historically been ingrained in Chinese society. However, it is uncertain to what extent these practices correspond to the global concept of a sustainable diet. In this study, we aimed to identify popular vegetarian dietary patterns in China based on the most-viewed online recipes and evaluate their associated food preferences and sustainability characteristics. The results indicated the following: (1) Chinese and Western vegetarian diets differ greatly in their food preferences for starchy staples, fruits, and dairy products. Popular Chinese vegetarian diets are characterized by high grain consumption and low intake of salt and added sugars. (2) Popular Chinese vegetarian diets are rich in vitamin E (32.37–37.36 mg/d), phosphorus (1172.80–1267.20 mg/d), copper (2.21–2.56 mg/d), and manganese (5.89–6.96 mg/d), yet deficient in vitamin A (421.03–565.65 μg RE/d), calcium (438.91–693.36 mg/d), and selenium (28.06–36.90 mg/d). Additionally, there is a risk of inadequate riboflavin intake within a vegan dietary pattern. (3) Compared with Chinese omnivorous diets and Western vegetarian diets, at the 2,000 kcal/d level, popular Chinese vegetarian diets have a lower environmental footprint in terms of land use (3.44–5.95 m2), greenhouse gas emissions (1.76–2.74 kgCO2eq), and freshwater withdrawals (510.87–678.34 L). Our findings serve as a valuable reference for promoting healthy dietary choices worldwide and advancing sustainable development goals related to food security and environmental conservation.